Math, asked by tanveerfatima0484, 10 months ago

expand each of the following using suite able identities(2a-3b)^3

Answers

Answered by Anonymous
5

Answer:

(2a-3b)^3=(a-b)^3

(a-b) ³ = a³-b³-3a²b+3ab²

(2a-3b)³= (2a)³-(3b)³- 3(2a)²(3b)+ 3(2a)(3b)²

8a³-27b³-36a²b+ 54ab²

hope this helps you... plzz mark as BRAINLIEST answer

Answered by renjithsonukrishna
4

Answer:

using identity : (a-b)3 = a3 - b3 - 3ab(a-b)

(2a - 3b)3 = (2a)3 - (3b)3 - 3*2a*3b (2a - 3b)

= 8a3 - 27b3 - 18ab * 2a + 18ab * 2b

= 8a3 - 27b3 - 36 a2b + 54ab2

i hope you understand

Similar questions